ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGUKURAN KEPUASAN MAHASISWA TERHADAP PELAYANAN KAMPUS UNIVERSITAS MUHAMMADIYAH JAMBI BERBASIS WEB - Nugraha, Hafiz; Marthiawati. H, Noneng; Gustinar, Gustinar (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2022)
Seeing the importance of measuring the level of student satisfaction with the service implementation of the education and learning system, a container for measuring the level of student satisfaction is needed. Student satisfaction and a good experience received by each student is one of the priorities prioritized by the University of Muhammadiyah Jambi in shaping the image or good name of the university. But unfortunately, so far, to measure the level of student satisfaction in having the experience of feeling the service of implementing the education and learning system and using existing facilities at the University, it is still in the form of a questionnaire in the form of paper which is distributed directly to students when students are going for the final semester exams with a fairly time-consuming process. time in procedures and calculations. so that there is no transparency in data collection that is accumulated directly through the system and does not become a waste of time, energy and paper. The purpose of this study is to analyze and design an Information System for Measuring Student Satisfaction on Web-Based Services for the University of Muhammadiyah Jambi Campus so that it can improve the services of the University of Muhammadiyah Jambi Campus. This design is made using the visual paradigm and using object-based modeling techniques to describe the analysis and design of the system, namely in the form of use case diagrams, class diagrams, and activity diagrams. This study resulted in a prototype design of an Information System for Measuring Student Satisfaction on Web-Based Services for the University of Muhammadiyah Jambi Campus. On this basis, an integrated system is needed, it is hoped that the system can increase the effectiveness and efficiency of implementation for the university in handling and implementing faster solutions related to services on the University campus of Muhammadiyah Jambi University.